The Dynamics of Personal Adjustment in Quranic Memorization Students: A Mixed-Methods Analysis of Self-Acceptance, Objective Self-Action, and Self-Confidence in Islamic Boarding Schools - M. Agung Rahmadi; Said Agil Husin Al Munawar; Achmad Syahid; Abdul Rahman Shaleh; Helsa Nasution (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the dynamics of personal adjustment in Quranic memorization students using a mixed methods approach, combining quantitative field analysis as primary data and meta-analysis as secondary data. The field study involved 515 students from two Indonesian Islamic boarding schools: Pesantren Tahfizh Daarul Qur'an and Yayasan Islamic Centre Sumatera Utara. The meta-analysis included 30 studies (N = 4,827) from international databases. The quantitative analysis showed a high level of personal adjustment among students (M = 3.66, SD = 0.52), with the highest score on acting objectively according to one's conditions and potential (M = 3.85, SD = 0.48). Regression analysis revealed that self-acceptance significantly predicted overall personal adjustment (β = 0.42, p < .001). The meta-analysis confirmed a positive relationship between self-acceptance and personal adjustment (r = 0.53, 95% CI [0.47, 0.59]). Moderator analysis indicated a stronger effect for female students (r = 0.58) than males (r = 0.49). These findings extend the research of Ahmad et al. (2022) and Rahma (2023) by identifying unique factors influencing personal adjustment of Quranic memorization students, such as memorization intensity (β = 0.31, p < .01) and social support in Quranic boarding schools (β = 0.28, p < .01). Additionally, the integration of primary and secondary data provides a comprehensive understanding of the dynamics of personal adjustment in Quranic memorization students, emphasizing the importance of evidence-based interventions to enhance the psychological well-being of these students.